(untitled) (gjstudies, 2021)
This research investigates the adoption of Integrated Reporting (IR) and its consequential impact on stakeholder decision-making processes, a domain that remainsunderexplored despite the growing prominence of IR frameworks. Moving beyondtraditional financial reporting analysis, this study introduces a novel methodologicalapproach by integrating qualitative content analysis of IR disclosures with a quantitative assessment of stakeholder engagement metrics, thereby creating a hybridevaluative model. The primary research question examines how the comprehensiveness and connectivity of information presented in IR influence the cognitiveprocessing and subsequent decisions of diverse stakeholder groups, including investors, employees, and community representatives. A secondary question probesthe mediating role of information asymmetry reduction in this relationship. Themethodology employs a longitudinal case-study design across three early-adopterorganizations from distinct sectors, combined with a controlled experimental survey distributed to a stratified sample of 450 stakeholders. The analysis utilizes aproprietary scoring mechanism for IR quality, developed from first principles, whichassesses the depth of connectivity between financial, social, environmental, and governance capitals. Results reveal a non-linear, threshold-based relationship betweenIR adoption quality and stakeholder decision efficacy. Specifically, decision-makingaccuracy and confidence improve significantly only after IR disclosures achieve aminimum threshold of strategic connectivity and future orientation, a finding thatchallenges linear assumptions in prior literature. Furthermore, the study identifiesa ’narrative coherence’ factor as a critical, previously unquantified mediator thatenhances stakeholder trust more than the volume of data presented. The conclusion posits that the impact of IR is contingent not on mere adoption but on theachievement of integrative thinking in report preparation, which in turn reframesstakeholder mental models. This research contributes original insights by delineating the specific mechanisms through which IR transforms information into actionable intelligence for stakeholders, offering a new framework for evaluating reportingeffectiveness that prioritizes qualitative integration over quantitative expansion.